GC-MS based metabolite profiling and antibacterial activity of torch ginger (Etlingera elatior) flowers extract - Maser, Wahyu Haryati; Purwoko, Agus; Yuliana, Nancy Dewi; Lubis, Linda Masniary; Khatib, Alfi (Gadjah Mada University, 2022)
Torch ginger (Etlingera elatior) flowers are well known for their antibacterial effects against Staphylococcus aureus, however, the active compounds are still unknown. The purpose of this study was to conduct GC-MS-based metabolite profiling of torch ginger flower and identify compounds correlated with its S. aureus antibacterial activity using Orthogonal Projection to Latent Structure (OPLS). Using the well diffusion method, the antibacterial activity of ethanol extract, hexane, chloroform, and ethyl acetate fractions with a concentration of 80 mg/mL were investigated. The ethyl acetate fraction inhibited S. aureus growth the most (diameter of inhibition zone, DIZ 13.00–13.20 mm), while the hexane (DIZ 9.55–10.05 mm) and chloroform (DIZ 10.00–11.00 mm) fractions had moderate inhibitory activity, but the ethanol extract had no antibacterial effect. Using OPLS analysis, the GC-MS metabolite profile of all extracts and fractions was linked with the profile of antibacterial activity. This analysis revealed that Dodecanoic acid, 5-Tetradecene, and n-Hexadecanoic acid were identified as the compounds that were significantly connected with antibacterial activity.